The deadly avalanche of Rigopiano (Itália): evidences of a constructed local scale disaster
In a context of enhancing development, namely using natural resources and amenities to attract investments and create jobs, local interests can undervalue the natural risks. Our work demonstrates how local decisions and private, and political issues can interplay increasing risks and converge in creating a small-scale disaster. On January 18th 2017, an avalanche of size 5 (200,000 m3) buried under 4 meters of snow the Rigopiano Hotel, in the National Park of Gran Sasso and Maiella, in Italy. In this four-star resort, 38 people were blocked inside when the avalanche hit. Two people, who fortuitously escaped the avalanche because they were outside the hotel, contacted the Operational Center for Emergency. Rescue activities started after some hours of misunderstanding about alarm truthfulness. After some days of frantic efforts, carried out 24h/24 by up to 330 people, 9 people were pulled out alive and in good conditions, whereas 29 victims were pulled from wreckage. Our research demonstrates how the coincidence of structural and contingent factors of natural and human origin converged into a disaster. Even though the resort was built on a very hazardous and unsafe location, and the high level of avalanche danger on that day, the loss of lives could have been avoided by timely evacuating the people. The final result is tightly related to weak risk awareness of local authorities, which only saw in the resort a job tank.